Development of the career success cards to improve the career maturity of senior high school students - Yusmi Zulfitri; Farida Aryani; Sahril Buchori (Program Studi bimbingan Konseling PPs UNM Makassar, 2023)
This study aims to produce career success cards as a guidance and counseling media to improve students’ career maturity. This study aims to discover: (1) the level of need for career success cards to improve the career maturity of senior high school students; (2) the prototype of career success cards to improve the career maturity of senior high school students; and (3) the validity and practicality of career success cards in improving the career maturity of senior high school students. The Borg & Gall 10-step research model was adapted into seven steps to conduct this study. The data were collected using interviews and questionnaires. The results of the study showed that: (1) the level of need for career success cards to improve the career maturity of senior high school students, especially the students at SMAN 01 Bombana, was high; (2) the prototype of career success cards consisted of job cards, information cards, fill-in cards, a guidebook, and a career reading text; and (3) the validity testing results showed that the utility, feasibility, and accuracy of career success cards were very good, while the practicality testing results showed that career success cards were valid and practical to be used in high schools, especially at SMAN 01 Bombana, to help students improve their career maturity.